Hydrothermal grown iron oxide films on the surface of titanium and conductive glasses and their current characteristics in water photolysis - Seitmagzimov, A.A.; Seitmagzimova, G.M.; Dzhanmuldaeva, Zh.K. (KSU publ., 2020)
The relevance of photolysis on semiconductor electrodes since the pioneer work of Fujishima and Honda on metallic titanium does not lose sharpness due to new possibilities for developing new materials, such as con-ductive glasses, for which photolysis cells with semi-transparent semiconductor layer can be created. We have compared properties of such glasses with a metal for hydrothermal conditions of iron oxide synthesis. Iron oxide films have also been obtained by introducing a number of cations to modify semiconductor systems (Fe2O3). It turned out that the nature of the substrate significantly affects the properties of the formed conductive film, which ultimately forms the level of anodic photocurrents in the layer of iron oxide semiconductor. We have investigated current characteristics of such films; it was shown that charging processes occur better on metallic titanium than on conductive glasses. We consider that the metal substrate significantly reduces regen-eration processes both in the semiconductor layer and at the interface. Thus, formed Ti/Fe2O3 electrolyte het-erojunction is more efficient than the conducting glass/Fe2O3 electrolyte system. However, this does not mean that glass is less promising for photolysis systems. It is necessary to achieve more acceptable conditions for the synthesis of semiconductor material.
Keywords: iron oxide; conductivity; spectrum; current-voltage characteristic; anode photocurrent; band gap; semiconductor; doping